2014
DOI: 10.1002/cmdc.201402431
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of a Highly Selective 5,6,7,8‐Tetrahydrobenzo[4,5]thieno[2,3‐d]pyrimidin‐4(3H)‐one SIRT2 Inhibitor that is Neuroprotective in an in vitro Parkinson’s Disease Model

Abstract: Sirtuins, NAD(+) -dependent histone deacetylases (HDACs), have recently emerged as potential therapeutic targets for the treatment of a variety of diseases. The discovery of potent and isoform-selective inhibitors of this enzyme family should provide chemical tools to help determine the roles of these targets and validate their therapeutic value. Herein, we report the discovery of a novel class of highly selective SIRT2 inhibitors, identified by pharmacophore screening. We report the identification and validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 84 publications
4
65
0
Order By: Relevance
“…coli and purified through affinity and size-exclusion chromatography as previously described in [38]. …”
Section: Methodsmentioning
confidence: 99%
“…coli and purified through affinity and size-exclusion chromatography as previously described in [38]. …”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that SIRT2 can produce either protective or detrimental effects on cell survival . Several experimental studies have suggested that SIRT2 reduction can produce beneficial effects on Parkinson's disease (PD) . Because cumulative evidence has indicated critical roles of oxidative stress in the pathogenesis of PD and other neurological diseases , it is of importance to investigate the potential relationship between SIRT2 and oxidative stress.…”
mentioning
confidence: 99%
“…Two further examples of potent Sirt2‐selective inhibitors with proven cellular activities are ICL‐SIRT078 (34) (Fig. ) and AEM2 (35) (Fig. ) .…”
Section: Small‐molecule Inhibitors Of Sirtuinsmentioning
confidence: 87%